INDOOR RADON RELATED WITH THE GEOLOGY IN ROMANIAN URBAN AGGLOMERATIONS (CLUJ-NAPOCA) - FLORICĂ, Ștefan; DICU, Tiberius; BURGHELE, Bety-Denissa; MOLDOVAN, Mircea; SZACSVAI, Kinga; ȚENTER, Anca; PAPP, Botond; BELDEAN, Simion; FLORICĂ, Ștefan; CATALINA, Tiberiu; TUNYAGI, Arthur; HORJU-DEAC, Cristina; et al. (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
Radon is a natural radioactive gas that occurs due to the radioactive decay of radium (226Ra) present in rocks which, in turn, cames from the radioactive decay of uranium (238U), a primordial natural element. Along with factors such as porosity, permeability and humidity of the rocks and soils, pressure and temperature, geology setting plays one of the most important roles in the release of radon into the environment. Depending on the mineralogical compositions and characteristics of the bedrock from a certain area, a higher or lower concentration of radioactive minerals can be found in the rocks, which will directly influence the level of radon in the atmosphere, implicitly the concentration of radon measured in houses. In this study, a six months concentration of radon (222Rn) was assessed in 256houses from Cluj-Napoca area using CR-39 nuclear track detectors. Correlations between the indoor radon levels and the geological setting was further analyzed. The aim is to better understand the influence of geology on the concentration of radon levels in homes, in order to further identify other risk areas in terms of exposure to radon. Further investigation is needed on other factors influencing the accumulation of radon in high concentrations indoor, such as ventilation, occupation patterns or constructive and architectural features for typical houses. Therefore, the results of this work are considered to be important for indoor radon management in Romania.